Clinical application of new technique that measures C4d for assessment of activation of classical complement pathway. Issue 2 (February 1988) - Davies, E T; Nasaruddin, B A; Alhaq, A; Senaldi, G; Vergani, D
Abstract : A new laser nephelometric technique that measures C4d for the assessment of the activation of the classical complement pathway was developed. C4d was isolated from other larger C4 related molecules at a final concentration of polyethylene glycol of 12% and then quantitated by laser nephelometry using a commercially available antiserum, which reacts with C4d determinants. C4d standard (100%) was produced by exhaustive activation of the classical pathway in pooled normal human serum using heat aggregated human immunoglobulin. Serial dilutions of the standard provided a reference curve against which clinical samples were read. Patients with rheumatoid arthritis showed significantly higher C4d values (mean 53.8%) than controls (21.7%; p less than 0.001). The technique proved accurate, rapid, and suitable for the routine laboratory evaluation of complement activation through the classical pathway, and it may be useful in the management of those conditions in which complement activation has a pathogenic role.